Tingkat Pengetahuan Ibu Tentang Growth Spurt Usia 0-12 Bulan di Puskesmas Klandasan Ilir - Desiy Fitriani; Dewi Ari Sasanti, Syafitriya Ningsih (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2021)
Introduction: In Balikpapan, the incidence of reproductive health disorders experienced by young women from infectious diseases is 1,111 sufferers. unwanted pregnancy 53 cases, abortion 11 cases, and sexual violence 149 cases. Methods: This type of research uses quantitative descriptive. The population is class X students with a total of 212 sooswi with a sample of 139 students from class X students with a simple random sampling method.Results: 139 respondents got good category as many as 42 respondents (30.22%), enough for 63 respondents (45.32%), less than 34 respondents (24.46%). Most of the young women in SMA Negeri 3 Balikpapan have quite good knowledge of reproductive health disorders. Conclusion: knowledge of adolescent girls at SMA Negeri 3 Balikpapan about reproductive health disorders is quite good